THE IMPACT OF LOYALTY AND RETALIATION ON ACCOUNTANTS’ PROPENSITY TO BLOW THE WHISTLE: AN EXPERIMENT - Muhammad Ridwan (Jurnal Manajemen Terapan dan Keuangan, 2017)
This study experimentally examines the effect of loyalty level and retaliation strength, on accountants’ propensity to blow the whistle (PBW) when faced with a serious wrongdoing. It is argued that individuals with higher levels of loyalty are more likely to blow the whistle than are individuals with lower levels of loyalty. Besides, it is expected that individuals facing a weak retaliation are more likely to blow the whistle than are individuals facing a strong retaliation. Seventy working students enrolled in post-graduate of accounting program in two Indonesia universities participated in the study. Participants responded to three hypothetical whistle-blowing scenarios on one of two conditions –i.e., strong or weak retaliation for whistleblowing, and completed an instrument that measured loyalty. This study examines the arguments using the 2x2 between subjects design. Unconsistent with the philosophical theory of Larmer (1992), Corvino (2002), and Vandekerckhove and Commers (2004), this study empirically finds that the level of loyalty does not affect their PBW. In other words, this study fails to obtain empirical evidence about the effect of loyalty level on PBW. Besides, unlike results reported by Arnold and Ponemon (1991) and Liyanarachchi and Newdick (2009), a significant effect of retaliation strength on participants’ PBW is not found.